Preparation method of wave-absorbing material, wave-absorbing material and application of wave-absorbing material

By coating polydopamine on MXene material and performing high-temperature annealing, the problems of unsatisfactory impedance matching and poor absorption capacity of MXene material are solved, and good impedance matching and excellent microwave absorption performance of the absorbing material are achieved.

CN119528216APending Publication Date: 2025-02-28SHENZHEN SUNWAY COMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422792.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

As an absorbing material, MXene material has problems such as unsatisfactory impedance matching and easy longitudinal aggregation, resulting in poor absorption capacity.

Method used

By mixing Ti3C2Tx, metal salt and water, Ti3C2Tx of metal ion intercalation is formed, and then the in-situ self-polymerization of dopamine is used to form a polydopamine coating, and finally high-temperature annealing treatment is performed under the protection of inert gas to obtain a wave absorbing material.

Benefits of technology

It achieves good impedance matching and excellent microwave absorption performance of the absorbing material, and improves the overall performance of the absorbing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528216A_ABST
    Figure CN119528216A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to the technical field of wave-absorbing materials, in particular to a preparation method of a wave-absorbing material, the wave-absorbing material and application of the wave-absorbing material. In the embodiment of the invention, the Ti3C2Tx can adsorb metal ions in water to the inside of a lamella of the Ti3C2Tx through an electrostatic adsorption effect, so that the Ti3C2Tx of a metal ion intercalation layer is formed. Then generating polydopamine on the surface of the metal ion intercalated Ti < 3 > C < 2 > T < x > by utilizing in-situ auto-polymerization of dopamine to obtain a precursor material; the precursor material is subjected to high-temperature annealing treatment, so that polydopamine in the precursor material can be carbonized to obtain amorphous carbon, metal ions are reduced into iron, cobalt and / or nickel, and Ti3C2Tx is decomposed to obtain TiO2 and amorphous carbon. Wherein the TiO2 particles and the amorphous carbon can generate more interfaces, defects and conductive paths, so that impedance matching of the wave-absorbing material can be optimized, and the wave-absorbing performance of the wave-absorbing material can be improved. In addition, the introduction of the magnetic material (iron, cobalt and / or nickel) can bring magnetic loss, so that the wave-absorbing performance of the wave-absorbing material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of absorbing materials, and in particular to a method for preparing absorbing materials, absorbing materials and applications thereof. Background Art

[0002] Electromagnetic wave absorbing materials (abbreviated as absorbing materials) refer to a type of functional materials that can effectively absorb or attenuate incident electromagnetic waves and convert their electromagnetic energy into heat energy and dissipate it or make it disappear due to interference. Absorbing materials are widely used in stealth technology and anti-electromagnetic interference technology.

[0003] An ideal microwave absorbing material should be thin, light, have a wide absorption bandwidth and strong absorption capacity. MXene is a new type of two-dimensional material with unique two-dimensional structure, rich and controllable surface functional groups, high specific surface area, high conductivity and low density. It is an ideal high-performance microwave absorbing material. However, MXene has poor impedance matching and is prone to longitudinal aggregation. As a microwave absorbing material, it still has problems such as poor absorption capacity. Summary of the invention

[0004] The embodiment of the present application provides an absorbing material, which has good impedance matching and excellent microwave absorption performance while having a thin thickness and light weight.

[0005] In a first aspect of the present application, a method for preparing an absorbing material is provided, the method comprising: x , a metal salt and water are mixed so that the metal salt dissociates into metal ions in the water, and the metal ions are adsorbed on the Ti3C2T x to obtain a first mixed solution; mixing the first mixed solution with a dopamine hydrochloride solution to obtain a second mixed solution, adjusting the pH value of the second mixed solution to alkaline, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T4 adsorbed with the metal ions. x to form a precursor material; under the protection of an inert gas, the precursor material is subjected to a high temperature annealing treatment to obtain a wave absorbing material; wherein the metal ions include at least one of iron ions, cobalt ions and nickel ions; during the high temperature annealing treatment, the polydopamine in the precursor material is carbonized to obtain amorphous carbon, the metal ions are reduced to metals, and the Ti3C2T x Decomposition gives TiO2 and amorphous carbon.

[0006] In the embodiments of the present application, Ti3C2T x The surface of Ti3C2T is negatively charged, which can adsorb metal ions in water to Ti3C2T xInside the sheet, a metal ion intercalated Ti3C2T x . Then, the in-situ self-polymerization of dopamine on the metal ion intercalated Ti3C2T x polydopamine is generated on the surface of the precursor material to obtain a precursor material; under the protection of an inert gas, the precursor material is subjected to a high temperature annealing treatment to carbonize the polydopamine in the precursor material to obtain amorphous carbon, and the metal ions are reduced to iron, cobalt and / or nickel, and Ti3C2T x Decompose to obtain TiO2 and amorphous carbon, thereby obtaining the absorbing material. Among them, the amorphous carbon and Ti3C2T x The decomposed amorphous carbon acts as a reducing agent to reduce metal ions to metal elements. TiO2 particles and amorphous carbon can produce more interfaces, defects and conductive paths, which are beneficial to optimize the impedance matching of the absorbing material and improve the absorbing performance of the absorbing material. In addition, the introduction of magnetic materials (iron, cobalt and / or nickel) can bring about magnetic losses including hysteresis loss, natural resonance and eddy current loss, thereby enhancing the absorbing performance of the absorbing material.

[0007] In some embodiments, in the first mixed solution, the Ti3C2T x The mass ratio of the metal salt is in the range of (3:1) to (4:1).

[0008] In some embodiments, the dopamine hydrochloride solution comprises a solvent and dopamine hydrochloride dissolved in the solvent; in the second mixed solution, the Ti3C2T x The mass ratio of the dopamine hydrochloride to the dopamine hydrochloride is 1:1.

[0009] In some embodiments, the amount of dopamine hydrochloride added per 40 ml of the solvent is 0.1 g.

[0010] In some embodiments, adjusting the pH value of the second mixed solution to alkaline includes: adjusting the pH value of the second mixed solution to 8-8.5.

[0011] In some embodiments, the high-temperature annealing treatment of the precursor material under the protection of an inert gas includes: placing the precursor material in a tubular furnace with an inert gas flowing therein, and heating the temperature in the tubular furnace at a heating rate of 2°C / min; when the temperature in the tubular furnace rises to a preset temperature, maintaining the temperature in the tubular furnace at the preset temperature for 2 hours, and then naturally cooling the temperature in the tubular furnace to room temperature; wherein the preset temperature is 800°C to 850°C.

[0012] In some embodiments, before the precursor material is subjected to high-temperature annealing under the protection of an inert gas, the method further comprises: washing and centrifuging the precursor material until the pH value of the upper centrifugal liquid obtained by the centrifugation is not less than 6.5; and freeze-drying the precursor material.

[0013] In some embodiments, the Ti3C2T x , metal salt and water to obtain a first mixed solution, the method further comprises: preparing Ti3C2T x , the preparation of Ti3C2T x The process includes: adding Ti3AlC2 powder into hydrofluoric acid to obtain Ti3C2T x ; Wherein, 5g of the Ti3AlC2 powder is added to every 100ml of the hydrofluoric acid.

[0014] In the second aspect of the present application, there is also provided an absorbing material, which is prepared according to the method described in the first aspect.

[0015] In the third aspect of the present application, there is also provided an application of an absorbing material prepared by the method described in the first aspect in the field of electromagnetic wave absorption.

[0016] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 It is a schematic diagram of the process of preparing the absorbing material provided in some embodiments of the present application. DETAILED DESCRIPTION

[0019] The principles and spirit of the present disclosure will be described below with reference to several exemplary embodiments shown in the accompanying drawings. It should be understood that the description of these specific embodiments is only to enable those skilled in the art to better understand and implement the present disclosure, and does not limit the scope of the present disclosure in any way. In the following description and claims, unless otherwise defined, all technical and scientific terms used herein have the meanings commonly understood by those of ordinary skill in the art.

[0020] As used herein, the term "including" and similar terms should be understood as open inclusion, i.e., "including but not limited to". The term "based on" should be understood as "based at least in part on". The term "one embodiment" or "the embodiment" should be understood as "at least one embodiment". The terms "first", "second", etc. may refer to different or the same objects, and are only used to distinguish the objects referred to, without implying a specific spatial order, temporal order, order of importance, etc. of the objects referred to.

[0021] With the rapid development of modern science and technology, absorbing materials are not only required to have excellent absorbing properties, but also have excellent comprehensive properties, and then applied to various industrial fields. The emergence of various new materials and new preparation methods has a great driving force on the preparation and development of absorbing materials, resulting in the continuous emergence of new absorbing materials and continuous improvement of performance. Magnetic metal powders (such as Ni, Co, Fe and their alloys, etc.) belong to magnetic loss-type absorbing materials, have high magnetic permeability, can absorb a large amount of electromagnetic waves, especially have excellent absorption performance for high-frequency electromagnetic waves, and are a feasible and promising absorbing material that can make up for the shortcomings of ferrite magnetic materials such as unsatisfactory high-frequency characteristics and high mass filling rate, but they also have defects such as high cost and high density. Carbon materials, as a new type of electrical loss-type absorbing material, have the advantages of light weight, good conductivity, low price, high temperature resistance, and corrosion resistance.

[0022] In order to improve the comprehensive performance of the absorbing material, the present invention provides a method for preparing the absorbing material by inserting metal ions into Ti3C2T x Polydopamine is coated on the Ti3C2T x Annealing treatment is performed to obtain the absorbing material; during the annealing process, polydopamine is converted into amorphous carbon, Ti3C2T x The microwave absorbing material prepared by the method has good impedance matching and exhibits good microwave absorption performance. In order to facilitate the reader to understand the present application, the following is a description of the present invention in conjunction with specific embodiments.

[0023] For example, Figure 1 The process of preparing the wave absorbing material provided in the embodiment of the present application is shown. Figure 1 , the method comprises the following steps:

[0024] Step 11: Ti3C2T x , a metal salt and water are mixed so that the metal salt dissociates into metal ions in the water, and the metal ions are adsorbed onto the Ti3C2T xinside the sheet layer to obtain a first mixed solution;

[0025] Ti3C2T in the embodiment of the present application x MXene materials. MXene materials are a class of metal carbon / nitrides with a two-dimensional layered structure, and their general chemical formula is M n+1 X n T x , where (n = 1-3), M represents early transition metals, such as Ti, Zr, V, Mo, etc.; X represents C or N elements, T x MXene is a surface group, usually -OH, -O, -F or -Cl. It is named MXene because it has a sheet structure similar to graphene.

[0026] In the embodiments of the present application, Ti3C2T x , metal salt and water are mixed to obtain a first mixed solution. The metal salt dissolves in water and dissociates into metal ions in the water. The metal salt includes at least one of an iron salt, a cobalt salt and a nickel salt. In certain embodiments of the present application, the cobalt salt may specifically be CoCl2·6H2O and / or Co(NO3)2·6H2O, the nickel salt may specifically be NiCl2·6H2O and / or Ni(NO3)2·6H2O, and the iron salt may specifically be FeCl3·6H2O and / or FeCl3·6H2O. Accordingly, the metal ions include cobalt ions (Co 2+ ), nickel ions (Ni 2+ ) and iron ions (Fe 3+ ) at least one of them. x With negative charge, Ti3C2T in the first mixed solution x Able to adsorb metal ions onto Ti3C2T through electrostatic adsorption x Inside the sheet, a metal ion intercalated Ti3C2T x Specifically, in some embodiments, Ti3C2T x Disperse in water to obtain a dispersion, add metal salt to the dispersion, and continue stirring the dispersion for a period of time (such as 1 hour) to obtain a first mixed solution.

[0027] In some embodiments, in order to further improve the absorbing performance of the absorbing material, Ti3C2T x The mass ratio of Ti3C2T to metal salt is in the range of (3:1) to (4:1). x A mass ratio of the metal salt greater than 4:1 or less than 3:1 is not conducive to improving the absorbing performance of the absorbing material.

[0028] In some embodiments, before step 11, the method further comprises: preparing Ti3C2Tx Ti3C2T can be prepared using Ti3AlC2 and hydrofluoric acid (HF). x That is, Ti3AlC2 is etched by HF to obtain Ti3C2T x For example, Ti3AlC2 powder can be added to a container filled with hydrofluoric acid, and the mixed solution in the container is continuously stirred at room temperature to separate a black solid (Ti3C2T x ), the black solid is repeatedly washed, and then dried to obtain Ti3C2T x Powder. Specifically, the stirring time can be 24 hours; the drying method can be vacuum drying, and the drying time is 24 hours. In some embodiments, the black solid can be separated from the mixed solution by centrifugation, and then the black solid is repeatedly washed with deionized water, and the black solid is separated from the deionized water by centrifugation until the pH value of the upper centrifuge liquid is not less than 6.5. In some embodiments, in order to prepare Ti3C2T x , the amount of Ti3AlC2 added to every 100ml of hydrofluoric acid is 5g.

[0029] Step 12: Mix the first mixed solution and the dopamine hydrochloride solution to obtain a second mixed solution, and adjust the pH value of the second mixed solution to alkaline, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T4 adsorbed with the metal ions. x to form a precursor material.

[0030] In some embodiments, the dopamine hydrochloride solution comprises a solvent and dopamine hydrochloride (C8H 12 ClNO2), and the amount of dopamine hydrochloride added in each 40ml solvent is 0.1g. In some embodiments, the solvent can specifically be anhydrous ethanol. The preparation method of the dopamine hydrochloride solution is as follows: dissolving dopamine hydrochloride in anhydrous ethanol, and completely dissolving the dopamine hydrochloride in the anhydrous ethanol by ultrasound to obtain a dopamine hydrochloride solution.

[0031] In some embodiments, a dopamine hydrochloride solution can be added to the first mixed solution to obtain a second mixed solution. Specifically, the pH value of the second mixed solution can be adjusted to 8 to 8.5 so that the polydopamine generated after the dopamine hydrochloride reaction can better wrap the Ti3C2T x In certain embodiments of the present application, ammonia water may be used to adjust the pH value of the second mixed solution.

[0032] In some embodiments, in order to further improve the comprehensive performance of the absorbing material, Ti3C2Tx The mass ratio with dopamine hydrochloride is 1:1.

[0033] In some embodiments, step 12 specifically includes: the first mixed solution and the dopamine hydrochloride solution are placed in a reaction vessel and mixed to obtain a second mixed solution, the pH value of the second mixed solution is adjusted to alkaline, and after the dopamine hydrochloride reacts to generate polydopamine and form a precursor material, the precursor material is separated from the mixture in the reaction vessel. For example, the precursor material can be separated from the mixture by centrifugation. The precipitate obtained by centrifuging the mixture includes the precursor material. After the precursor material is separated from the mixture in the reaction vessel, the precursor material can also be repeatedly washed with deionized water, and the number of washings can be 3 times, 4 times or 5 times, etc. The centrifugal processing speed can be 8000rpm.

[0034] In some embodiments, after the precursor material is repeatedly washed, the pre-treated material needs to be dried to obtain a precursor material powder; the drying method can be freeze drying. Freeze drying means first cooling the water-containing precursor material to freeze it into a solid, and then directly sublimating the water in the precursor material under vacuum conditions, while the precursor material itself remains in the ice shelf during freezing. Therefore, the volume of the precursor material remains almost unchanged before and after freeze drying, and the original structure is maintained, which is loose and porous.

[0035] Step 13: Under the protection of an inert gas, the precursor material is subjected to a high-temperature annealing treatment to obtain a microwave absorbing material.

[0036] Specifically, the precursor material can be placed in a tubular furnace with an inert gas flowing, and the temperature in the tubular furnace can be heated at a heating rate of 2°C / min; when the temperature in the tubular furnace is heated to a preset temperature, the temperature in the tubular furnace is maintained at the preset temperature for 2 hours, and then the temperature in the tubular furnace is naturally cooled to room temperature; wherein the preset temperature is 800°C to 850°C. In certain embodiments of the present application, the precursor powder can be first spread in a porcelain boat, and then the porcelain boat containing the precursor powder is placed in a tubular furnace for high-temperature annealing. The inert gas can be nitrogen or argon, etc.

[0037] In this embodiment, under the protection of an inert gas, the precursor material is subjected to a high temperature annealing treatment to carbonize the polydopamine in the precursor material to obtain amorphous carbon. x The carbonized amorphous carbon and TiO2 were precipitated on the surface of the amorphous carbon. xThe decomposed amorphous carbon acts as a reducing agent to reduce metal ions to metal elements (such as iron, cobalt and / or nickel). Among them, TiO2 particles and amorphous carbon can produce more interfaces, defects and conductive paths, which are conducive to optimizing the impedance matching of the absorbing material and improving the absorbing performance of the absorbing material. In addition, the introduction of magnetic metal materials (such as iron, cobalt and / or nickel) can bring about magnetic losses including hysteresis loss, natural resonance and eddy current loss, thereby further enhancing the absorbing performance of the absorbing material.

[0038] Several embodiments of the present application are provided below.

[0039] Example 1

[0040] (1) 5 g of Ti3AlC2 powder was slowly added to a container containing 100 ml of hydrofluoric acid. The mixture in the container was continuously stirred at room temperature for 24 h, and then the black reaction product was separated from the mixture in the container by centrifugation. The reaction product was washed with deionized water several times, and the reaction product in the deionized water was separated by centrifugation until the pH value of the upper centrifuge liquid was 6.5; the reaction product was vacuum dried for 24 h to obtain Ti3C2T x powder.

[0041] (2) 0.15 g Ti3C2T x The powder was dispersed in 30 ml of deionized water to obtain Ti3C2T x A dispersion in deionized water; after adding 0.03 g of CoCl2·6H2O and 0.02 g of NiCl2·6H2O to the dispersion, stirring was continued for 1 hour to obtain a first mixed solution.

[0042] Dissolve 0.15 g of dopamine hydrochloride in 60 ml of anhydrous ethanol to obtain a dopamine hydrochloride solution.

[0043] The first mixed solution and the dopamine hydrochloride solution are mixed, and the pH value of the mixture of the first mixed solution and the dopamine hydrochloride solution is adjusted to 8 by ammonia water, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T4 adsorbed with the metal ions. x to form a precursor material. The precursor material is washed and centrifuged until the pH value of the upper centrifugal liquid obtained by centrifugation is not less than 6.5, and then the precursor material is freeze-dried to obtain a precursor material powder. The precursor material powder is placed in a tubular furnace with a nitrogen atmosphere, and the temperature in the tubular furnace is heated at a heating rate of 2°C / min; when the temperature in the tubular furnace is heated to 800°C, the temperature in the tubular furnace is maintained at 800°C for 2h, and then the temperature in the tubular furnace is naturally cooled to room temperature to obtain the absorbing material converted from the precursor material.

[0044] Example 2

[0045] (1) 5 g of Ti3AlC2 powder was slowly added to a container containing 100 ml of hydrofluoric acid. The mixture in the container was continuously stirred at room temperature for 24 h, and then the black reaction product was separated from the mixture in the container by centrifugation. The reaction product was washed with deionized water several times, and the reaction product in the deionized water was separated by centrifugation until the pH value of the upper centrifuge liquid was 6.5; the reaction product was vacuum dried for 24 h to obtain Ti3C2T x powder.

[0046] (2) 0.20 g Ti3C2T x The powder was dispersed in 30 ml of deionized water to obtain a dispersion of Ti3AlC2 in deionized water; 0.02 g of FeCl3·6H2O and 0.03 g of CoCl2·6H2O were added to the dispersion and stirred for 1 hour to obtain a first mixed solution.

[0047] Dissolve 0.2 g of dopamine hydrochloride in 80 ml of anhydrous ethanol to obtain a dopamine hydrochloride solution.

[0048] The first mixed solution and the dopamine hydrochloride solution are mixed, and the pH value of the mixture of the first mixed solution and the dopamine hydrochloride solution is adjusted to 8.5 by ammonia water, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T4 adsorbed with the metal ions. x to form a precursor material. The precursor material is washed and centrifuged until the pH value of the upper centrifugal liquid obtained by centrifugation is not less than 6.5, and then the precursor material is freeze-dried to obtain a precursor material powder. The precursor material powder is placed in a tubular furnace with a nitrogen atmosphere, and the temperature in the tubular furnace is heated at a heating rate of 2°C / min; when the temperature in the tubular furnace is heated to 850°C, the temperature in the tubular furnace is maintained at 850°C for 2h, and then the temperature in the tubular furnace is naturally cooled to room temperature to obtain the absorbing material converted from the precursor material.

[0049] Comparative Example 1

[0050] (1) Slowly add 5 g of Ti3AlC2 powder to a container containing 100 ml of hydrofluoric acid. After continuously stirring the mixture in the container for 24 hours at room temperature, separate the black reaction product from the mixture in the container by centrifugation. Wash the reaction product several times with deionized water and separate the reaction product in the deionized water by centrifugation until the pH value of the upper centrifuge liquid is 6.5; vacuum dry the reaction product for 24 hours to obtain Ti3AlC2 powder.

[0051] (2) 0.15 g Ti3C2T x The powder was dispersed in 30 ml of deionized water to obtain Ti3C2T x Dispersion in deionized water.

[0052] Dissolve 0.2 g of dopamine hydrochloride in 80 ml of anhydrous ethanol to obtain a dopamine hydrochloride solution.

[0053] The first mixed solution and the dopamine hydrochloride solution are mixed, and the pH value of the mixture of the first mixed solution and the dopamine hydrochloride solution is adjusted to 8 by ammonia water, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T x to form a precursor material. The precursor material is washed and centrifuged until the pH value of the upper centrifugal liquid obtained by centrifugation is not less than 6.5, and then the precursor material is freeze-dried to obtain a precursor material powder. The precursor material powder is placed in a tubular furnace with a nitrogen atmosphere, and the temperature in the tubular furnace is heated at a heating rate of 2°C / min; when the temperature in the tubular furnace is heated to 850°C, the temperature in the tubular furnace is maintained at 850°C for 2h, and then the temperature in the tubular furnace is naturally cooled to room temperature to obtain the absorbing material converted from the precursor material.

[0054] Table 1 shows the performance of the absorbing materials provided in Examples 1-2 and Comparative Example 1. It can be seen from Table 1 that the optimal thickness of the absorbing material provided in Example 1 (the absorbing performance of the absorbing material is best at this thickness) is 2.80 mm, and the minimum reflection loss value (RL min ) is -52.4dB, and the effective absorption bandwidth (EAB) is 7.25GHz; the optimal thickness of the absorbing material provided in Example 2 is 2.30mm, and the minimum reflection loss value (RL min ) is -45.8dB, and the effective absorption bandwidth (EAB) is 6.26GHz; the optimal thickness of the absorbing material provided in Comparative Example 1 is 2.00mm, and the minimum reflection loss value (RL min ) is -20.20dB, and the effective absorption bandwidth (EAB) is 4.26GHz. Compared with Comparative Example 1, the minimum reflection loss value of the absorbing material provided by Example 1 and Example 2 is smaller, so Example 1 and Example 2 have better absorbing performance. At the same time, compared with Comparative Example 1, Example 1 and Example 2 can effectively broaden the effective absorption bandwidth of the absorbing material.

[0055] Table 1

[0056]

[0057] In the embodiments of the present application, Ti3C2Tx The surface of Ti3C2T is negatively charged, which can adsorb metal ions in water to Ti3C2T x Inside the sheet, a metal ion intercalated Ti3C2T x . Then, the in-situ self-polymerization of dopamine on the metal ion intercalated Ti3C2T x polydopamine is generated on the surface of the precursor material to obtain a precursor material; under the protection of an inert gas, the precursor material is subjected to a high temperature annealing treatment to carbonize the polydopamine in the precursor material to obtain amorphous carbon, and the metal ions are reduced to iron, cobalt and / or nickel, and Ti3C2T x Decomposition produces amorphous carbon and TiO2 with excellent dielectric properties, thereby obtaining an absorbing material. Among them, the amorphous carbon and Ti3C2T x The decomposed amorphous carbon acts as a reducing agent to reduce metal ions to metal elements. TiO2 particles and amorphous carbon can produce more interfaces, defects and conductive paths, which are beneficial to optimize the impedance matching of the absorbing material and improve the absorbing performance of the absorbing material. In addition, the introduction of magnetic materials (iron, cobalt and / or nickel) can bring about magnetic losses including hysteresis loss, natural resonance and eddy current loss, thereby enhancing the absorbing performance of the absorbing material. The absorbing material provided in the embodiment of the present application can absorb electromagnetic waves in a coordinated manner through dielectric loss and magnetic loss.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they may still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a microwave absorbing material, characterized in that: The method comprises: Ti3C2T x , a metal salt and water are mixed so that the metal salt dissociates into metal ions in the water, and the metal ions are adsorbed onto the Ti3C2T x inside the sheet layer to obtain a first mixed solution; The first mixed solution and the dopamine hydrochloride solution are mixed to obtain a second mixed solution, and the pH value of the second mixed solution is adjusted to alkaline, so that the dopamine hydrochloride in the second mixed solution reacts to generate polydopamine, and the polydopamine is coated on the Ti3C2T4 adsorbed with the metal ions. x On, forming a precursor material; Under the protection of an inert gas, the precursor material is subjected to a high temperature annealing treatment to obtain a microwave absorbing material; Wherein, the metal ions include at least one of iron ions, cobalt ions and nickel ions; During the high temperature annealing treatment, the polydopamine in the precursor material is carbonized to obtain amorphous carbon, the metal ions are reduced to metals, and the Ti3C2T x Decomposition gives TiO2 and amorphous carbon.

2. The method according to claim 1, characterized in that In the first mixed solution, the Ti3C2T x The mass ratio of the metal salt is in the range of (3:1) to (4:1).

3. The method according to claim 1, characterized in that The dopamine hydrochloride solution comprises a solvent and dopamine hydrochloride dissolved in the solvent; In the second mixed solution, the Ti3C2T x The mass ratio of the dopamine hydrochloride to the dopamine hydrochloride is 1:

1.

4. The method according to claim 3, characterized in that The amount of dopamine hydrochloride added per 40 ml of the solvent was 0.1 g.

5. The method according to claim 1, characterized in that The step of adjusting the pH value of the second mixed solution to alkaline comprises: The pH value of the second mixed solution is adjusted to 8-8.

5.

6. The method according to claim 1, characterized in that The step of subjecting the precursor material to high temperature annealing under the protection of an inert gas comprises: Placing the precursor material in a tube furnace with an inert gas flowing therein, and heating the tube furnace at a heating rate of 2°C / min; When the temperature in the tube furnace rises to a preset temperature, the temperature in the tube furnace is maintained at the preset temperature for 2 hours, and then the temperature in the tube furnace is naturally cooled to room temperature; Wherein, the preset temperature is 800°C to 850°C.

7. The method according to claim 1, characterized in that Before the precursor material is subjected to high temperature annealing under the protection of an inert gas, the method further comprises: Washing and centrifuging the precursor material until the pH value of the upper centrifugal liquid obtained by the centrifugation is not less than 6.5; The precursor material is freeze-dried.

8. The method according to any one of claims 1 to 7, characterized in that: The Ti3C2T x , the metal salt and water are mixed to obtain a first mixed solution, the method further comprises: Preparation of Ti3C2T x , the preparation of Ti3C2T x include: Ti3AlC2 powder is added to hydrofluoric acid to obtain Ti3C2T x ; Wherein, 5 g of the Ti3AlC2 powder is added to every 100 ml of the hydrofluoric acid.

9. A wave absorbing material, characterized in that: The absorbing material is prepared according to the method according to any one of claims 1-8.

10. Use of the absorbing material prepared by the method according to any one of claims 1 to 8 in the field of electromagnetic wave absorption.